The Associations of Serum Osteocalcin and Cortisol Levels With the Psychological Performance in Primary Hyperparathyroidism Patients - Wang, Shu-min; He, Yang; Zhu, Min-ting; Tao, Bei; Zhao, Hong-yan; Sun, Li-hao; Liu, Jian-min (Frontiers in Endocrinology, 2021)
Objectives The aim of this study was to investigate factors responsible for the psychological performance in primary hyperparathyroidism (PHPT) patients. Methods A group of 38 PHPT patients receiving questionnaires, including Beck Depression Inventory (BDI), State–Trait Anxiety Inventory (STAI), and 36-Item Short Form Survey (SF-36), was evaluated. The relationships between scores of questionnaires and clinical biomarkers were examined. Collinearity and linear regression model were applied to examine variables determining the scores of the questionnaire. In 192 PHPT patients, bivariate and partial correlation were used to analyze the relationships between serum concentrations of parathyroid hormone (PTH), calcium, osteocalcin (OCN), and cortisol. Results Among 38 patients receiving questionnaire tests, 50% (19/38) of the patients developed state anxiety, 60.5% (23/38) of the patients had the trait of developing anxiety. In addition, 18.4% (7/38) of the patients developed mild to severe depression. Serum cortisol at 8:00 was negatively and significantly correlated with social function (r = -0.389, p = 0.041) after controlling for age, sex, disease duration, serum PTH, calcium, phosphorus, and 25-hydroxyvitamin D [25(OH)D] concentration. OCN was significantly and negatively correlated with score of STAI-S (r = -0.426, p = 0.027). In the linear regression model for BDI score, variables with statistical significance were serum OCN (β = -0.422, p = 0.019) and cortisol at 0:00 (β = 0.371, p = 0.037). In 192 PHPT patients, the serum concentration of OCN (r = 0.373, p = 0.000) was positively correlated with PTH level. After controlling for age, sex, disease duration, serum 25(OH)D, phosphorus, and calcium concentration, the positive correlation between OCN and PTH was still statistically significant (r = 0.323, p = 0.000). The serum concentration of cortisol at 0:00 was significantly and positively correlated with serum calcium (r = 0.246, p = 0.001) in bivariate correlation analysis. After controlling for age, sex, disease duration, serum PTH, 25(OH)D, and phosphorus concentration, serum cortisol at 0:00 was still positively and significantly correlated with serum calcium (r = 0.245, p = 0.001). Conclusion Serum levels of OCN and cortisol, rather than PTH and calcium, are associated with the development of anxiety and depression symptoms in PHPT patients.